Устройство для моделирования трехфазного многообмоточного трансформатора - Боровиков Ю. С. Юрий Сергеевич; Сулайманов А. О. Алмаз Омурзакович; Андреев М. В. Михаил Владимирович; Гусев А. С. Александр Сергеевич; Прутик А. Ф. Алексей Фёдорович; Гордиенко И. С. Иван Сергеевич
опубл. 10.04.13